FRI0248 PROGNOSTIC FACTORS FOR STEROID-FREE REMISSION IN PATIENTS WITH IDIOPATHIC INFLAMMATORY MYOPATHIES: IMPORTANCE OF ANTHROPOMETRIC MEASUREMENTS. (2nd June 2020) - Lee, J. S.; Nam, S. H.; Choi, S. J.; Seo, W. J.; Hong, S.; Lee, C. K.; Yoo, B.; Oh, J. S.; Kim, Y. G.
Abstract : Background: Several studies have been conducted on factors associated with mortality in idiopathic inflammatory myopathies (IIM), but few studies have assessed prognostic factors for steroid-free remission in IIM. Objectives: We investigated the various clinical factors, including body measurements, that affect IIM treatment outcomes. Methods: Patients who were newly diagnosed with IIM between 2000 and 2018 were included. Steroid-free remission was defined as at least three months of normalisation of muscle enzymes and no detectable clinical disease activity. The factors associated with steroid-free remission were evaluated by a Cox regression analysis. Results: Of the 106 IIM patients, 35 displayed steroid-free remission during follow-up periods. In the multivariable Cox regression analyses, immunosuppressants' early use within one month after diagnosis [hazard ratio (HR) 6.21, 95% confidence interval (CI) 2.61–14.74, p < 0.001] and sex-specific height quartiles (second and third quartiles versus first quartile, HR 3.65, 95% CI 1.40–9.51, p = 0.008 and HR 2.88, 95% CI 1.13–7.32, p = 0.027, respectively) were positively associated with steroid-free remission. Polymyositis versus dermatomyositis (HR 0.21, 95% CI 0.09–0.53, p = 0.001), presence of dysphagia (HR 0.15, CI 0.05–0.50, p = 0.002) and highest versus lowest quartile of waist circumference (WC) (HR 0.24, 95% CI 0.07–0.85, p = 0.027) were negatively associated with steroid-free remission. Conclusion: The early initiation of immunosuppressant therapy, type of myositis and presence of dysphagia are strong predictors of steroid-free remission in IIM; moreover, height and WC measurements at baseline may provide additional important prognostic value. Disclosure of Interests: None declared